Role of Kagocel® in the treatment of recurrent herpes virus infections - Yuliya E. Dobrokhotova; Irina N. Kononova; Tatiana A. Ogurtsova (Клинический разбор в общей медицине)
The article provides a brief overview of the conceptual approach to the treatment of genital herpesvirus infections, a review of studies on the use of the interferon inducers Kagocel® in complex therapy of genital herpes, demonstrates clinical observations of a patient with recurrent genital herpesvirus infection, a patient with an exacerbation of genital herpesvirus infection that is difficult to respond to standard therapy, a patient with genital herpes, poorly controlled by acyclic nucleosides.